Identitas Nasional Dalam Bingkai Negara Indonesia - Fanny Melawati Lisdiana; Ilham Sudrajat; Mutiara Zaskia Kiran (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Indonesia certainly has its own uniqueness and identity, this makes national identity necessary for all nations and countries, especially the state of Indonesia. National identity itself even becomes a sign, characteristic, characteristic, and identity that can differentiate it from others both in terms of religion, culture, language, goals, even the aspirations of the nation and state. In Indonesia itself, of course, national identity is a differentiatornfrom other nations and countries based on Pancasila, whose embodiment can be realized innthe lifenof thennation and state.iThis paper aimsi to understandxand describe national identity. Thisnstudyvuses a descriptivexapproach method whose basic discussionwisxobtained frommvariouszexisting sources,ynamely journalsxand articles. Withithentopicnraised,onamely National Identity,lthe writer is interestedcin analyzingnthis because itnis verysimportant tokdevelopiknowledge that is veryqimportantiforqthe nationrand state.